High-temperature-resistant insulating material as well as preparation method and application thereof

By introducing trifluoromethyl groups and HTP crosslinking agents into polyetherimide, a mesoscopic ordered phase structure is constructed, which solves the problem of performance degradation of high-temperature resistant insulating materials at high temperatures and achieves ultra-high insulation performance under high temperature and high field conditions. It is suitable for insulating materials for ultra-high voltage DC power transmission and new energy vehicles.

CN121203201APending Publication Date: 2025-12-26HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511520945.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Existing high-temperature resistant insulation materials exhibit deterioration in insulation performance at 150℃ and a sharp decline in performance under high-frequency operating conditions, making it difficult to meet the extreme operating conditions required by ultra-high voltage direct current transmission systems and new energy vehicles.

Method used

Using HFBAPP, 6FDA and HTP as the main raw materials, a mesoscopic ordered phase structure with continuous periodicity is constructed by introducing trifluoromethyl groups into polyetherimide. HTP is used to enhance the stability of the mesoscopic ordered phase, forming a multi-level density heterostructure. Combined with a crosslinking agent, a bridged covalent network is formed to balance the requirements of short-range densification and mesoscopic loosening.

Benefits of technology

It achieves ultra-high insulation performance with a breakdown field strength of ≥800MV/m at 150℃, which improves the dielectric insulation performance of the material under high temperature and high field conditions, and is suitable for insulation materials for high voltage flexible DC transmission and new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121203201A_ABST
    Figure CN121203201A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant insulating material as well as a preparation method and application thereof, and belongs to the technical field of functional polymer composite materials and preparation thereof. The high-temperature-resistant insulating material solves the problems that the insulating property of an existing high-temperature-resistant insulating material is degraded at the temperature of 150 DEG C, and the performance of the existing high-temperature-resistant insulating A-CF3 group is introduced into polyetherimide, a mesoscopic sequential phase structure with continuous periodicity is induced for the first time by utilizing the steric hindrance effect and the electrostatic repulsion effect of the polyetherimide, and the limitation of a traditional crystal-amorphous binary structure is broken through. Furthermore, the stability of the mesoscopic sequential phase is enhanced through a topological cross-linking agent (HTP), a density heterostructure is formed by the mesoscopic sequential phase structure and a short-range ordered domain to remarkably inhibit carrier migration, and the ultrahigh insulation performance of 800 MV / m or above is achieved at the temperature of 150 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a kind of high-temperature-resistant insulating materials and its preparation method and application, belong to functional polymer composite material and its preparation technical field. BACKGROUND

[0002] With the popularization of extra-high voltage DC transmission system and new energy vehicle 800V platform, the insulating materials for electrical equipment face the challenge of extreme working conditions: it needs to realize the breakdown field strength ≥700MV / m and high-frequency low loss (tan δ≤0.005 at 150kHz) at 150℃ high temperature.

[0003] The current research direction of improving the performance of insulating materials at high temperature focuses on high-temperature-resistant aromatic polyphenyl polymers, but the π-π stacking within and between the chains will form a continuous conjugated channel, which will cause the carrier to surge. The research on traditional polymer dielectric focuses on the regulation of local short-range ordered structure, and the mechanism of how the macroscopic arrangement of molecular chains systematically affects the dielectric properties is still insufficient.

[0004] The above bottleneck leads to the degradation of the insulating performance of existing materials at 150℃, and the performance of high-frequency working conditions decays sharply. Therefore, it is urgent to develop a breakthrough in the traditional polymer research and development method based on the regulation strategy of mesoscopic molecular chain structure, to break through the high-temperature performance bottleneck of polymer insulating materials for electrical equipment. SUMMARY

[0005] The present application provides a kind of high-temperature-resistant insulating materials and its preparation method and application to solve the problem of the degradation of the insulating performance of existing high-temperature-resistant insulating materials at 150℃, and the performance of high-frequency working conditions decays sharply.

[0006] The technical scheme of the present application is as follows: One of the purposes of the present application is to provide a preparation method of high-temperature-resistant insulating materials, which comprises the following steps: (1) Dissolve HFBAPP in a dehydrated and deoxygenated polar aprotic solvent under vacuum, 0-5℃, and inert atmosphere protection, stir for 15-30min, to obtain a diamine solution; (2) Under vacuum, 0-5℃, and inert atmosphere protection, add 6FDA powder to the diamine solution of (1) in batches, and stir for 5-6h to obtain an FPAA solution; (3) At 15-25℃, add HTP to the FPAA solution, stir for 10-16h to obtain an FPAA / HTP solution; (4) Under vacuum degree ≤10 -3 Pa, room temperature, the FPAA / HTP solution is subjected to step-by-step degassing treatment, then the wet film obtained by solution casting is subjected to thermal imidization treatment to obtain a high-temperature-resistant insulating material.

[0007] Further limitation, the polar aprotic solvent in (1) is DMAC.

[0008] Further limitation, the ratio of the total moles of 6FDA added to the moles of HFBAPP in (2) is 1:1.008-1:015.

[0009] Further limitation, the temperature fluctuation of the system is ≤±1℃ when 6FDA is added in (2) in batches.

[0010] Further limitation, the stirring speed in (2) is 200-300rpm.

[0011] Further limitation, the mass of HTP added in (3) is 0.3% of the mass of HFBAPP.

[0012] Further limitation, the solid content of the FPAA / HTP solution obtained in (3) is 18-22wt%.

[0013] Further limitation, the temperature of the FPAA / HTP solution during the coating process in (4) is 20±0.5℃, and the viscosity is 2500±200cP.

[0014] Further limitation, the coating conditions in (4) are: ultra-dry inert atmosphere, relative humidity ≤1%, oxygen content ≤1ppm.

[0015] Further limitation, the thickness of the wet film in (4) is 4-9μm.

[0016] Further limitation, the heat imidization process in (4) is: increasing to 80℃ at 1℃ / min, keeping for 5.5-6.5h, then increasing to 100℃ at 2℃ / min, keeping for 0.8-1.2h, then increasing to 150℃ at 3℃ / min, keeping for 0.8-1.2h, then increasing to 200℃ at 5℃ / min, keeping for 0.8-1.2h, and finally increasing to 275±2℃ at 8℃ / min, keeping for 0.8-1.2h.

[0017] The second object of the present application is to provide a high-temperature-resistant insulating material prepared by the above method, and specifically, the breakdown field strength of the high-temperature-resistant insulating material at 150℃ is ≥800MV / m.

[0018] The third object of the present application is to provide an application of the above high-temperature-resistant insulating material, and specifically, the high-temperature-resistant insulating material is used for the insulation of high-voltage flexible direct current transmission and conversion electrical equipment and new energy automobile insulation in working environment temperature ≥125℃ and working field strength ≥300MV / m.

[0019] Advantages: The application constructs a polyetherimide system with HFBAPP as a diamine, 6FDA as a dianhydride, and HTP as a crosslinking agent. By introducing a trifluoromethyl (-CF3) group into the polyetherimide, the mesoscopically ordered phase (MOP) structure with continuous periodicity is first induced by using the steric hindrance effect and electrostatic repulsion. The mesoscopically ordered phase stability is strengthened by a topological crosslinking agent (HTP), breaking through the limitation of traditional crystal-amorphous binary structure, and then breaking through the performance limit of dielectric insulating materials under high temperature and high field. Compared with the prior art, at least the following advantages are obtained: (1) The -CF3 group in the polyetherimide insulating material prepared by the application triggers deep rearrangement of molecular chains through a triple synergistic mechanism, forming a mesoscopic periodic order, and the -CF3 group significantly improves the conformational rigidity (dihedral angle increases by 30°) through the sigma bond induction effect, providing a conformational basis for mesoscopic order. At the same time, the steric hindrance effect of the -CF3 group and the electrostatic repulsion between groups significantly expand the interchain distance, inhibit chain entanglement, and drive the molecular chains to arrange in a mesoscopic periodicity, inducing a mesoscopically ordered phase (MOP) structure with continuous periodicity, breaking through the limitation of traditional crystal-amorphous binary structure, and presenting a continuous periodic arrangement of molecular chains at a mesoscopic scale (5-20 nm), constructing a density heterostructure, and breaking through the performance limit of dielectric insulating materials under high temperature and high field, realizing an ultra-high insulation performance of more than 800 MV / m at 150 DEG C.

[0020] (2) The plurality of -CF3 groups in the high-temperature-resistant insulating material prepared by the application form a strong local dipole moment, reconfigure the polarity microenvironment of the polymer, enhance the dipole-dipole interaction, and improve the packing density of the inherent short-range ordered region in the system. The residual amine group (-NH) and the fluorine atom form an N-H···F hydrogen bond, further stabilizing the dense arrangement of the short-range ordered microzone, thereby strengthening the dense packing of the local short-range ordered microzone, and maintaining the long-range mesoscopic periodicity by electrostatic repulsion, realizing the spatial coupling of the mesoscopically ordered phase and the short-range ordered domain in the density heterostructure, producing a significant polymer density spatial heterogeneity, constructing a density heterostructure by using the density fluctuation between the MOP and the local short-range ordered domain, and forming a high-efficiency carrier trap at the interface of the electronic potential barrier gradient, fundamentally reconfiguring the electrical response behavior of the polymer, and further using the density heterogeneity at the mesoscopic scale to construct a localized charge trap domain, thereby realizing the precise regulation of the charge storage and dissipation behavior of the polymer material.

[0021] (3) The present application uses HTP as a crosslinking agent, and forms a "bridging type" covalent network through the dihedral angle of biphenyl and the polyamine group. The amine group fixes the short-range order, and the π-π stacking and the rigid biphenyl skeleton extend the mesoscopic periodicity, so that the low-angle diffraction peak intensity is improved. This "rigid-flexible" crosslinking strategy effectively balances the needs of short-range densification and mesoscopic loosening, and finally realizes the construction of a multi-level density heterogeneous structure with short-range ordered clusters and mesoscopic ordered structures. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 XRD comparison spectrum of the insulating materials prepared for Comparative Examples 1-5; Figure 2 XRD comparison spectrum of the insulating materials prepared for Comparative Example 1 and Example 1-4; Figure 3 Dielectric spectrum of the insulating materials prepared for Comparative Examples 1-5; Figure 4 Dielectric spectrum of the insulating materials prepared for Comparative Example 1 and Example 1-4; Figure 5 Leakage current density diagram of Comparative Examples 1-5; Figure 6 Leakage current density diagram of the insulating materials prepared for Comparative Example 1 and Example 1-4; Figure 7 Breakdown result diagram of the insulating materials prepared for Comparative Examples 1-5; Figure 8 Breakdown result diagram of the insulating materials prepared for Comparative Example 1 and Example 1-4. DETAILED DESCRIPTION

[0023] In order to make the above objectives, features and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application will be described in detail below with reference to the description examples.

[0024] In the following description, a large number of specific details are set forth in order to facilitate a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without departing from the connotation of the present application, therefore the present application is not limited to the specific embodiments disclosed below.

[0025] Secondly, "one embodiment" or "embodiment" referred to herein means that specific features, structures or characteristics can be included in at least one implementation of the present application. "In one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is it an embodiment that is separate or alternative to other embodiments.

[0026] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used, unless specifically stated, are conventional materials, reagents, methods and instruments in the art, which are available to those skilled in the art through commercial channels.

[0027] 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP), CAS No. 69563-88-8; 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), CAS No. 1107-00-2; 2,4,6-triaminopyrimidine (TP), CAS No. 1004-38-2; 5''-(4'-amino-[1,1'-biphenyl]-4-yl)-[1,1':4',1'':3'',1''':4''',1'''-quaterphenyl]-4,4''''- diamine (HTP), CAS No. 1400987-00-9; solvent N,N-dimethylacetamide (DMAC), CAS No. 127-19-5 used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used, unless specifically stated, are conventional materials, reagents, methods and instruments in the art, which are available to those skilled in the art through commercial channels.

[0028] Comparative Example 1 The method for preparing the insulating material fluorinated polyetherimide (FPEI) in this comparative example includes the following steps: Step 1: 0.906249 g of HFBAPP was dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent under vacuum (vacuum degree -0.1 MPa) and deep low temperature (5°C) for low-temperature monomer activation stirring for 25 min.

[0029] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of step 1, 6FDA powder with a total amount of 0.784296 g was slowly added in 4 batches to the solution of step 1, the feeding rate was controlled to make the system temperature fluctuate ≤±1°C, and the reaction was carried out under 250 rpm mechanical stirring for 2 h to obtain FPAA solution.

[0030] Step 3: The solution obtained in step 2 was first degassed under vacuum ≤10 -3 Pa, room temperature, stirring equipment speed 10 rpm for 15 min, then remove the stirring equipment under vacuum -0.1 MPa for 4 h, completely remove the micro-bubbles.

[0031] Step 4: The degassed solution obtained in step 3 was subjected to a casting film process in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) box, a precision doctor blade was used to control the wet film thickness in the range of 5 μm, the precursor solution temperature was controlled at 20±0.5°C during film coating, and the viscosity was controlled at 2500±200 cP.

[0032] Step 5: The wet film obtained in step 4 is subjected to an imidization oven drying heating process by an oven, and the specific temperature rising steps are as follows: 1 ℃ / min to 80 ℃ for 6 h, then 2 ℃ / min to 100 ℃ for 1 h, then 3 ℃ / min to 150 ℃ for 1 h, then 5 ℃ / min to 200 ℃ for 1 h, and finally 8 ℃ / min to 275±2 ℃ for 1 h.

[0033] Step 6: The film is peeled off under the assistance of deionized water at 40 ℃ and ultrasonic waves, and then dried by using an up-and-down double-temperature air flow control technology. Specifically, after the oven is vacuumized, argon is introduced, the upper layer is set to 80 ℃, and the lower layer is set to 60 ℃. The self-balancing field formed by the hot convection is used to accelerate the drying process, and finally the insulating material fluorinated polyetherimide is obtained, which is named FPEI.

[0034] Comparative Example 2 The method for preparing the insulating material cross-linked fluorinated polyetherimide (FPEI / 0.1wt%TP) in this comparative example includes the following steps: Step 1: Under vacuum (vacuum degree-0.1 MPa) and deep low temperature (5 ℃), 0.905343 g of HFBAPP is dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent to perform low-temperature monomer activation stirring for 25 min.

[0035] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of step 1, 6FDA powder with a total amount of 0.784296 g is slowly added in 4 batches to the solution of step 1, the feeding rate is controlled to make the system temperature fluctuate ≤±1 ℃, and the reaction is performed under 250 rpm mechanical stirring for 2 h to obtain an FPAA solution. 0.000145 g of TP particles pre-dried at 60 ℃ for 24 h is slowly added to the FPAA solution, the blending temperature is controlled at 15-25 ℃, and the stirring is continued for 15 h to ensure the formation of a cross-linked network, thereby obtaining a uniform, stable and phase-separated FPAA / 0.1wt%TP solution.

[0036] Step 3: The FPAA / 0.1wt%TP solution obtained in step 2 is degassed in a vacuum chamber with a vacuum degree ≤10 -3 Pa and room temperature, and the stirring equipment is rotated at 10 rpm for 15 min, and then the stirring equipment is removed and placed under vacuum-0.1 MPa for 4 h to completely remove the micro-bubbles.

[0037] Step 4: The degassed solution obtained in step 3 is subjected to a casting film process in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) chamber, and the wet film thickness is controlled within 5 μm by using a precision doctor blade. The temperature of the precursor solution is controlled at 20±0.5 ℃, and the viscosity is controlled at 2500±200 cP during the film coating.

[0038] Step 5: The wet film obtained in step 4 is subjected to an imidization oven drying heating process by an oven, and the specific temperature rising steps are as follows: 1°C / min to 80°C for 6h, then 2°C / min to 100°C for 1h, then 3°C / min to 150°C for 1h, then 5°C / min to 200°C for 1h, and finally 8°C / min to 275±2°C for 1h.

[0039] Step 6: The film is peeled off under the assistance of deionized water at 40°C and ultrasonic waves, and then dried by using the upper and lower double-temperature air flow control technology. Specifically, after the oven is vacuumized, argon is introduced, the upper layer is set to 80°C, and the lower box is set to 60°C. The self-balancing field formed by the heat convection is used to accelerate the drying process, and finally the cross-linked fluorinated polyether imide insulating material is obtained, which is named FPEI / 0.1wt%TP.

[0040] Comparative Example 3: The method for preparing the cross-linked fluorinated polyether imide insulating material (FPEI / 0.2wt%TP) of the present comparative example comprises the following steps: Step 1: Under vacuum (vacuum degree -0.1 MPa) and deep low temperature (5°C), 0.904437g of HFBAPP is dissolved in 10ml of N,N-dimethylacetamide (DMAC) solvent, and low-temperature monomer activation stirring is carried out for 25min.

[0041] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of step 1, 0.784296g of 6FDA powder is slowly added to the solution of step 1 in 4 batches, the feeding rate is controlled to make the system temperature fluctuate ≤±1°C, and the reaction is carried out under 250rpm mechanical stirring for 2h to obtain the FPAA solution. 0.000291g of TP particles pre-dried at 60°C for 24h are slowly added to the FPAA solution, the blending temperature is controlled at 15-25°C, and the stirring is continued for 15h to ensure the formation of cross-linked network, obtaining a uniform, stable and phase-separated FPAA / 0.2wt%TP solution.

[0042] Step 3: The FPAA / 0.2wt%TP solution obtained in step 2 is subjected to a vacuum degree ≤10 -3 Pa, room temperature, stirring equipment speed 10rpm, stirring for 15min, then removing the stirring equipment under vacuum-0.1MPa for 4h, and completely removing the micro-bubbles.

[0043] Step 4: The degassed solution obtained in step 3 was cast in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) cabinet, and a precision doctor blade was used to control the wet film thickness in the range of 5 pm. The temperature of the precursor solution was controlled at 20±0.5°C, and the viscosity was controlled at 2500±200 cP during the film coating process.

[0044] Step 5: The wet film obtained in step 4 was subjected to an imidization oven drying heating process. The specific temperature rising steps were as follows: 1°C / min to 80°C for 6 h, then 2°C / min to 100°C for 1 h, then 3°C / min to 150°C for 1 h, then 5°C / min to 200°C for 1 h, and finally 8°C / min to 275±2°C for 1 h.

[0045] Step 6: The film was peeled off at 40°C in deionized water and under the assistance of ultrasonic waves, and then dried using an upper and lower temperature airflow control technology. Specifically, after vacuumizing the oven, argon was introduced, the upper layer was set to 80°C, and the lower cabinet was set to 60°C. A self-balancing field was formed by using thermal convection to accelerate the drying process, and finally the cross-linked fluorinated polyether imide insulating material, named FPEI / 0.2wt%TP, was obtained.

[0046] Comparative Example 4: The method for preparing the cross-linked fluorinated polyether imide insulating material (FPEI / 0.3wt%TP) of this comparative example included the following steps: Step 1: Under vacuum (vacuum degree -0.1 MPa) and deep low temperature (5°C), 0.903531 g of HFBAPP was dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent, and low-temperature monomer activation stirring was performed for 25 min.

[0047] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of step 1, 0.784296 g of 6FDA powder was slowly added in 4 batches to the solution of step 1, the feeding rate was controlled to make the system temperature fluctuate ≤±1°C, and the reaction was carried out for 2 h under 250 rpm mechanical stirring to obtain an FPAA solution. 0.000437 g of TP particles pre-dried at 60°C for 24 h were slowly added to the FPAA solution, the blending temperature was controlled at 15-25°C, and continuous stirring was performed for 15 h to ensure the formation of a cross-linked network, obtaining a uniform, stable, and phase-separated FPAA / 0.3wt%TP solution.

[0048] Step 3: The FPAA / 0.3wt%TP solution obtained in step 2 was degassed in a vacuum degree ≤10 -3 Pa, room temperature, and stirring equipment speed 10 rpm for 15 min, and then the stirring equipment was removed and placed under vacuum -0.1 MPa for 4 h to completely remove the micro-bubbles.

[0049] Step 4: The degassed solution obtained in Step 3 was subjected to a casting process in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) cabinet, and a precision doctor blade was used to control the wet film thickness in the range of 5 pm. The temperature of the precursor solution was controlled at 20±0.5°C, and the viscosity was controlled at 2500±200 cP during the film coating process.

[0050] Step 5: The wet film obtained in Step 4 was subjected to an imidization oven drying heating process, and the specific temperature rising steps were as follows: 1°C / min to 80°C for 5 h, then 2°C / min to 100°C for 1 h, then 3°C / min to 150°C for 1 h, then 5°C / min to 200°C for 1 h, and finally 8°C / min to 275±2°C for 1 h.

[0051] Step 6: The film was peeled off under the assistance of deionized water at 40°C and ultrasonic waves, and then dried using an up-and-down double-temperature air flow control technology. Specifically, after the oven was vacuumed, argon was introduced, the upper layer was set to 80°C, and the lower cabinet was set to 60°C. A self-balancing field was formed by using thermal convection to accelerate the drying process, and finally the cross-linked fluorinated polyether imide insulating material, named FPEI / 0.3wt%TP, was obtained.

[0052] Comparative Example 5: The method for preparing the cross-linked fluorinated polyether imide insulating material (FPEI / 0.3wt%TP) of this comparative example included the following steps: Step 1: Under vacuum (vacuum degree -0.1 MPa) and deep low temperature (5°C), 0.902624 g of HFBAPP was dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent, and the low-temperature monomer activation stirring was performed for 25 min.

[0053] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of Step 1, 0.784296 g of 6FDA powder was slowly added in 4 batches to the solution of Step 1, the feeding rate was controlled to make the system temperature fluctuate ≤±1°C, and the reaction was performed for 2 h under 250 rpm mechanical stirring to obtain an FPAA solution. 0.000583 g of TP particles pre-dried at 60°C for 24 h were slowly added to the FPAA solution, the blending temperature was controlled at 15-25°C, and the stirring was continued for 15 h to ensure the formation of a cross-linked network, obtaining a uniform, stable, and phase-separated FPAA / 0.4wt%TP solution.

[0054] Step 3: The FPAA / 0.4wt%TP solution obtained in Step 2 was degassed in a vacuum degree ≤10 -3Pa, stirring at 10 rpm for 15 min at room temperature, then removing the stirring device and allowing it to stand for 4 h under vacuum at -0.1 MPa to completely remove microbubbles.

[0055] Step 4: The degassed solution obtained in Step 3 is subjected to a flow coating process in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) box, and a precision doctor blade is used to control the wet film thickness in the range of 5 μm. The temperature of the precursor solution is controlled at 20±0.5°C during coating, and the viscosity is controlled at 2500±200 cP.

[0056] Step 5: The wet film obtained in Step 4 is subjected to an imidization oven drying heating process, and the specific temperature rising steps are as follows: 1°C / min to 80°C for 6 h, then 2°C / min to 100°C for 1 h, then 3°C / min to 150°C for 1 h, then 5°C / min to 200°C for 1 h, and finally 8°C / min to 275±2°C for 1 h.

[0057] Step 6: The film is peeled off at 40°C in deionized water and under ultrasonic assistance, and then dried using an up-and-down double-temperature air flow control technique. Specifically, after the oven is evacuated, argon is introduced, the upper layer is set to 80°C, and the lower box is set to 60°C. A self-balancing field is formed by using thermal convection to accelerate the drying process, and finally the crosslinked fluorinated polyether imide insulating material, designated as FPEI / 0.4wt%TP, is obtained.

[0058] Example 1: The method for preparing the crosslinked fluorinated polyether imide insulating material (FPEI / 0.1wt%HTP) of this example includes the following steps: Step 1: Under vacuum (vacuum degree -0.1 MPa) and deep low temperature (5°C), 0.905343 g of HFBAPP is dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent, and low-temperature monomer activation stirring is performed for 25 min.

[0059] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of Step 1, 0.784296 g of 6FDA powder is slowly added in 4 batches to the solution of Step 1, the feeding rate is controlled to make the system temperature fluctuate ≤±1°C, and the reaction is carried out under 250 rpm mechanical stirring for 2 h to obtain an FPAA solution. 0.000675 g of HTP particles pre-dried at 60°C for 24 h is slowly added to the FPAA solution, and the blending temperature is controlled at 15-25°C. Continuous stirring is performed for 15 h to ensure the formation of a crosslinked network, and a uniform, stable, and phase-separated FPAA / 0.1wt%HTP solution is obtained.

[0060] Step 3: The FPAA / 0.1 wt% HTP solution obtained in Step 2 was degassed under vacuum of ≤10 -3 Pa, at room temperature, under stirring at 10 rpm for 15 minutes, followed by removing the stirring device and standing for 4 h under vacuum -0.1 MPa to completely remove micro-bubbles.

[0061] Step 4: The degassed solution obtained in Step 3 was cast in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) box, and a precision doctor blade was used to control the wet film thickness within 5 pm. The temperature of the precursor solution was controlled at 20±0.5°C, and the viscosity was controlled at 2500±200 cP during the film coating process.

[0062] Step 5: The wet film obtained in Step 4 was subjected to imidization drying heating process by an oven, and the specific temperature rising steps were as follows: 1°C / min to 80°C for 6 h, then 2°C / min to 100°C for 1 h, then 3°C / min to 150°C for 1 h, then 5°C / min to 200°C for 1 h, and finally 8°C / min to 275±2°C for 1 h.

[0063] Step 6: The film was peeled off under the assistance of deionized water at 40°C and ultrasonic waves, followed by drying using an up-and-down double-temperature air flow control technology. Specifically, after vacuumizing the oven, argon was introduced, the upper layer was set to 80°C, and the lower box was set to 60°C. A self-balancing field was formed by using thermal convection to accelerate the drying process, and finally the cross-linked fluorinated polyetherimide insulating material, named FPAA / 0.1 wt% HTP, was obtained.

[0064] Example 2: The method for preparing the cross-linked fluorinated polyetherimide insulating material (FPEI / 0.2 wt% HTP) of this example includes the following steps: Step 1: Under vacuum (-0.1 MPa) and deep low temperature (5°C), 0.904437 g of HFBAPP was dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent to perform low-temperature monomer activation stirring for 25 min.

[0065] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of Step 1, 0.784296 g of 6FDA powder was slowly added in 4 batches to the solution of Step 1, the feeding rate was controlled to make the system temperature fluctuate ≤±1°C, and the reaction was carried out under 250 rpm mechanical stirring for 2 h to obtain a FPAA solution. 0.001351 g of HTP particles pre-dried at 60°C for 24 h was slowly added to the FPAA solution, and the blending temperature was controlled at 15-25°C. The stirring was continued for 15 h to ensure the formation of a cross-linked network, and a uniform, stable, and phase-separated FPAA / 0.2 wt% HTP solution was obtained.

[0066] Step 3: The FPAA / 0.2wt%HTP solution obtained in Step 2 was degassed under vacuum (vacuum degree≤10 -3 Pa, room temperature, stirring equipment speed 10 rpm for 15 minutes, then remove the stirring equipment under vacuum-0.1 MPa for 4 h, completely remove the micro-bubbles.

[0067] Step 4: The degassed solution obtained in Step 3 was cast in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) box, and the wet film thickness was controlled within 5 μm using a precision doctor blade. The temperature of the precursor solution was controlled at 20±0.5℃, and the viscosity was controlled at 2500±200 cP during the coating process.

[0068] Step 5: The wet film obtained in Step 4 was subjected to imidization oven drying heating process by oven, the specific procedure was: 1℃ / min to 80℃ for 6h, then 2℃ / min to 100℃ for 1h, then 3℃ / min to 150℃ for 1h, then 5℃ / min to 200℃ for 1h, finally 8℃ / min to 275±2℃ for 1h.

[0069] Step 6: The film was peeled off at 40℃ deionized water and ultrasonic assistance, then dried by using up and down double temperature airflow control technology, specifically, after vacuumizing the oven, argon was introduced, and the upper layer temperature was set to 80℃, and the lower box was set to 60℃, using thermal convection to form a self-balancing field to accelerate the drying process, finally obtaining the insulating material cross-linked fluorinated polyether imide, named FPAA / 0.2wt%HTP.

[0070] Example 3: The method for preparing the insulating material cross-linked fluorinated polyether imide (FPEI / 0.3wt%HTP) of this example includes the following steps: Step 1: Under vacuum (vacuum degree-0.1 MPa) and deep low temperature (5℃), 0.903531 g of HFBAPP was dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent, and the monomer was activated and stirred for 25 min.

[0071] Step 2: Under the condition of maintaining the low temperature and inert atmosphere of step 1, 0.784296 g of 6FDA powder was added into the solution of step 1 in 4 batches, and the feeding rate was controlled to make the system temperature fluctuate ≤±1℃, and the reaction was carried out for 2h under mechanical stirring at 250 rpm to obtain the FPAA solution. 0.002026 g of HTP particles pre-dried at 60℃ for 24h was slowly added into the FPAA solution, and the blending temperature was controlled at 15-25℃, and the stirring was continued for 15h to ensure the formation of cross-linked network to obtain a uniform, stable and no phase separation FPAA / 0.3wt%HTP solution.

[0072] Step 3: The FPAA / 0.3wt%HTP solution obtained in step 2 was degassed in a vacuum chamber with a vacuum degree ≤10 -3 Pa, room temperature, stirring equipment speed 10 rpm for 15 minutes, and then the stirring equipment was removed and placed under vacuum-0.1 MPa for 4h to completely remove the micro-bubbles.

[0073] Step 4: The degassed solution obtained in step 3 was cast in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) box, and a precision doctor blade was used to control the wet film thickness in the range of 5 μm, and the temperature of the precursor solution was controlled at 20±0.5℃ during the film coating, and the viscosity was controlled at 2500±200 cP.

[0074] Step 5: The wet film obtained in step 4 was subjected to imidization drying heating process by oven, and the specific temperature rising steps were as follows: 1℃ / min to 80℃ for 6h, then 2℃ / min to 100℃ for 1h, then 3℃ / min to 150℃ for 1h, then 5℃ / min to 200℃ for 1h, and finally 8℃ / min to 275±2℃ for 1h.

[0075] Step 6: The film was peeled off under the condition of deionized water at 40℃ and ultrasonic assistance, and then dried by using the upper and lower temperature airflow control technology, specifically, after vacuumizing the oven, argon was introduced, and the upper layer temperature was set to 80℃, and the lower box was set to 60℃, and the self-balancing field formed by the heat convection was used to accelerate the drying process, and finally the cross-linked fluorinated polyether imide insulating material, named FPAA / 0.3wt%HTP, was obtained.

[0076] Example 4: The method for preparing the cross-linked fluorinated polyether imide insulating material (FPEI / 0.4wt%HTP) of this example includes the following steps: Step 1: Under the condition of vacuum (vacuum degree-0.1 MPa) and deep low temperature (5℃), 0.902624 g of HFBAPP was dissolved in 10 ml of N,N-dimethylacetamide (DMAC) solvent, and the low-temperature monomer activation stirring was carried out for 25 min.

[0077] Step 2: Under the conditions of maintaining the low temperature and inert atmosphere of step 1, 0.784296 g of 6FDA powder was slowly added in 4 batches to the solution of step 1, the feeding rate was controlled to make the system temperature fluctuate ≤±1℃, and the reaction was carried out under mechanical stirring at 250 rpm for 2 h to obtain the FPAA solution. 0.002702 g of HTP particles pre-dried at 60℃ for 24 h were slowly added to the FPAA solution, the blending temperature was controlled at 15-25℃, and the stirring was continued for 15 h to ensure the formation of cross-linked network, obtaining a uniform, stable, and no phase separation FPAA / 0.4wt%HTP solution.

[0078] Step 3: The FPAA / 0.4wt%HTP solution obtained in step 2 was stirred in a vacuum degree ≤10 -3 Pa, room temperature, stirring equipment speed 10 rpm for 15 minutes, then remove the stirring equipment under vacuum-0.1 MPa for 4 h, completely remove the micro-bubbles.

[0079] Step 4: The degassed solution obtained in step 3 was cast in an ultra-dry inert atmosphere (water content <0.1 ppm, oxygen content <0.1 ppm) box, and a precision doctor blade was used to control the wet film thickness in the range of 5 μm. The temperature of the precursor solution was controlled at 20±0.5℃, and the viscosity was controlled at 2500±200 cP during the film coating process.

[0080] Step 5: The wet film obtained in step 4 was subjected to imidization drying heating process by oven, the specific temperature rising steps were as follows: 1℃ / min to 80℃ for 6h, then 2℃ / min to 100℃ for 1h, then 3℃ / min to 150℃ for 1h, then 5℃ / min to 200℃ for 1h, and finally 8℃ / min to 275±2℃ for 1h.

[0081] Step 6: The film was peeled off under the assistance of deionized water at 40℃ and ultrasonic wave, and then dried by using the up-down double-temperature air flow control technology. Specifically, after vacuumizing the oven, argon was introduced, the upper layer temperature was set to 80℃, and the lower box was set to 60℃. The self-balancing field formed by the hot convection was used to accelerate the drying process, and finally the cross-linked fluorinated polyetherimide insulating material was obtained, which was named FPAA / 0.4wt%HTP.

[0082] Effect example: (1) The XRD comparison spectrum of the insulating materials prepared in Examples 1-4 and Comparative Examples 1-5 is shown in Figure 1. Figures 1-2As shown in the figure, using TP as a crosslinking agent forms a rigid three-dimensional network through high-energy imide bonds, forcing the FPEI chain segments to pack tightly. This results in an increase in the intensity of the short-range ordered peaks corresponding to the high-angle diffraction peaks, and a significant reduction in the interchain spacing. However, its rigid covalent bonds disrupt the long-range spacing regulation maintained by the electrostatic repulsion of -CF3, leading to a decrease in the intensity of the low-angle diffraction peaks. In contrast, the long-chain polyaniline derivative HTP forms a "bridging" covalent network with polyamine groups through the dihedral angle of biphenyl. This enhances short-range order through amino group fixation and expands the mesoscopic periodicity by utilizing its π-π stacking and the rigid biphenyl framework, thus improving the intensity of the low-angle diffraction peaks. This "rigid-flexible" crosslinking strategy effectively balances the needs of short-range compaction and mesoscopic loosening, ultimately constructing a multi-level density heterostructure that combines short-range ordered clusters and mesoscopic ordered phases. This structural feature suppresses carrier migration through the interfacial electronic barrier gradient while maintaining free volume expansion, providing a key microstructure basis for subsequent breakthroughs in insulation performance.

[0083] (2) Dielectric spectra of the insulating materials prepared in Examples 1-4 and Comparative Examples 1-5, as shown in the figure. Figures 3-4 As shown in the figure, regarding the regulation of dielectric constant (ε'), for both TP and HTP covalently cross-linked systems, the dielectric constant exhibits a monotonically decreasing trend with increasing cross-linking agent content. This inhibitory effect is primarily due to the covalent cross-linking reaction consuming the polar groups on the FPEI chain, reducing the polar group density of the system; secondly, the rigid three-dimensional covalent network formed by the cross-linked structure restricts the rotational degrees of freedom of the polymer chain segments, significantly suppressing dipole orientation polarization. This demonstrates the synergistic regulatory effect of the hierarchical ordered heterostructure on the material's polarization behavior (dielectric constant) and energy dissipation (dielectric loss).

[0084] (3) Leakage current density diagrams of the insulating materials prepared in Examples 1-4 and Comparative Examples 1-5 at 150°C, as shown in the figure. Figures 5-6 As shown in the figure, the leakage current density of FPEI / 0.3wt% HTP is reduced by an order of magnitude compared to FPEI / 0.3wt% TP. This leap is attributed to a triple synergistic mechanism: the suppression of carrier mobility by cross-linking traps; and the reduction of polarization / conduction losses by confined chain dynamics. This demonstrates the key role of cross-linked-induced enhanced mesoscopic ordered phase / locally ordered multilevel density heterostructure, confirming the unique advantages of mesoscopic ordered phase / locally ordered multilevel density heterostructure in high-temperature insulation.

[0085] (4) Breakdown diagrams of the insulating materials prepared in Examples 1-4 and Comparative Examples 1-5 at 150°C, as shown in the figure. Figures 7-8As shown in the figure, FPEI / 0.3wt%HTP achieved ultra-high insulation performance of more than 800MV / m at 150℃. This is because TP builds a strong three-dimensional network through high-strength covalent bonds, which severely limits the mobility of polymer chains and the ability of electric field-induced orientation. This makes it difficult for molecular chains to undergo significant deformation or form local high-field strength areas (hot spots) under strong electric fields, thereby effectively inhibiting the initiation of electrical breakdown. The high bond energy and irreversibility inherent in covalent bonds give the network excellent long-term stability and durability, and can effectively block the development path of electrical treeing. Even under long-term electrical stress, the network can still maintain structural integrity, giving the polymer excellent anti-breakdown performance. HTP, on the other hand, uses its extended biphenyl chain to build a covalently cross-linked network that combines rigidity and moderate flexibility. Under the action of an electric field, its aromatic conjugate fragments can effectively absorb high-energy electrons, reducing the probability of collision ionization. This structure significantly enhances the polymer's ability to resist electric field-induced polarization and carrier transport, while making potential breakdown paths highly tortuous. This greatly reduces the probability of electron tunneling and the formation and development of electrical trees, thereby efficiently improving the anti-breakdown performance. In summary, by precisely designing the cross-linking chemistry and the topological structure of the cross-linking agent, a cross-linked network with a specific ordered hierarchy can be built, which can synergistically regulate the electronic structure, carrier behavior, chain segment dynamics, and mechanical response, ultimately achieving a significant and differentiated improvement in dielectric breakdown strength.

[0086] The above merely describes preferred embodiments of the present application, and those skilled in the art can make appropriate changes and modifications to the above embodiments. Therefore, the present application is not limited to the above specific embodiments, and some modifications and changes of the present application should fall within the protection scope of the claims of the present application.

Claims

1. A method for preparing a high-temperature resistant insulating material, characterized in that, include: (1) Under vacuum, 0-5℃ and inert atmosphere protection, HFBAPP is dissolved in a dehydrated and deoxygenated polar aprotic solvent and stirred for 15-30 min to obtain a diamine solution. (2) Under vacuum, 0-5℃ and inert atmosphere protection, 6FDA powder was added in batches to the diamine solution of (1), and the reaction was stirred for 5-6 hours to obtain FPAA solution; (3) At 15-25℃, add HTP to the FPAA solution and stir for 10-16h to obtain the FPAA / HTP solution; (4) When the vacuum degree is ≤10 -3 At room temperature and Pa, the FPAA / HTP solution was subjected to a stepwise degassing treatment, and then a film was coated using a solution casting method. The resulting wet film was then subjected to thermal imidization treatment to obtain a high-temperature resistant insulating material.

2. The preparation method according to claim 1, characterized in that, (1) The neutral polar aprotic solvent is DMAC.

3. The preparation method according to claim 1, characterized in that, (2) The ratio of the total molar amount of 6FDA to the molar amount of HFBAPP is 1:1.008-1:

015.

4. The preparation method according to claim 1, characterized in that, (3) The mass of HTP added is 0.3% of the mass of HFBAPP.

5. The preparation method according to claim 1, characterized in that, (3) The solid content of the obtained FPAA / HTP solution is 18-22 wt%.

6. The preparation method according to claim 1, characterized in that, (4) The conditions for the intermediate coating are: ultra-dry inert atmosphere, relative humidity ≤1%, oxygen content ≤1ppm.

7. The preparation method according to claim 1, characterized in that, (4) The thickness of the wet film is 4-9 μm.

8. The preparation method according to claim 1, characterized in that, (4) The medium-temperature imidization process is as follows: heat up to 80℃ at 1℃ / min and keep for 5.5-6.5h, then heat up to 100℃ at 2℃ / min and keep for 0.8-1.2h, then heat up to 150℃ at 3℃ / min and keep for 0.8-1.2h, then heat up to 200℃ at 5℃ / min and keep for 0.8-1.2h, and finally heat up to 275±2℃ at 8℃ / min and keep for 0.8-1.2h.

9. A high-temperature resistant insulating material prepared by the method according to any one of claims 1 to 8, characterized in that, The insulation material has a breakdown field strength of ≥800MV / m at 150℃.

10. An application of the high-temperature resistant insulating material according to claim 9, characterized in that, Insulation for high-voltage flexible DC transmission converter electrical equipment with working environment temperature ≥125℃ and working field strength ≥300MV / m, and insulation for new energy vehicles.